Patients Eagerness for 2nd Eye External Dacryocystorhinostomy after the Satisfactory Surgery of 1st Eye in Tertiary Care Hospital of Islamabad Suburbs - Matloob, Afia; Akhtar, Waseem; Yousafzai, Erum (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine patient satisfaction with successful external dacryocystorhinostomy for one eye and patients’ preference time for second eye dacryocystorhinostomy after the first surgery. Study Design: Prospective longitudinal study. Place and Duration of Study: Department of Ophthalmology, HBS General Hospital, Islamabad Pakistan, from Jan 2018 to Dec 2020. Methodology: A sample of 37 patients was calculated. All selected patients underwent bilateral external dacryocystorhinostomy and were followed for six months. Patient satisfaction was measured using a treatment satisfaction scale. Results: A total of 37 patients were included in the study. The mean age of patients was 33.5 ± 3.1 years. Satisfaction with 1st eye external DCR was extremely satisfied in 14 (37.8%), satisfied in 14 (37.8%), neutral in 2 (5.4%), dissatisfied in 6 (16.2%) and extremely dissatisfied 1 (2.6%). 31 (83.8%) prefer second eye surgery in ≤1 year after first eye DCR, while 6 (16.2%) prefer second eye surgery after more than one year of first eye DCR surgery. The majority of females prefer ≤1 year duration for second eye DCR surgery as compared to males 25 (67.7%) vs 6 (16.2%), (p=0.03). Anatomical success and functional success were insignificantly associated with satisfaction of first eye DCR surgery of patients (p=0.793 and p=0.482) Conclusions: High satisfaction with first eye dacryocystorhinostomy and greater preference for second eye dacryocystorhinostomy was found in patients coming to tertiary care hospital in Pakistan.